Forage productivity and soil properties in dual‐purpose cover crop systems. (18th October 2021) - Simon, Logan M.; Obour, Augustine K.; Holman, Johnathon D.; Johnson, Sandy K.; Roozeboom, Kraig L.
Abstract: Intensification of dryland cropping systems with cover crops (CCs) in the semi‐arid central Great Plains could enhance soil health and diversify production when used for forage. This study was conducted from 2015 to 2020 to determine forage mass, nutritive value of CCs, and effects of dual‐purpose CCs on soil properties in a no‐till winter wheat ( Triticum aestivum L.)–grain sorghum [ Sorghum bicolor (L.) Moench]–fallow cropping system. Treatments were oat ( Avena sativa L.)/triticale (× Triticosecale Wittm.) CCs grown in place of fallow, which were hayed, grazed by yearling heifers, or left standing. Forage mass varied across years and averaged 3, 546 kg ha −1 for standing CCs. Hayed and grazed CCs removed 73 and 26% of available forage. Soil bulk density was unaffected by haying or grazing compared to standing CCs. Soil organic carbon (SOC) stocks in the 0‐to‐15‐cm depth in 2019 were similar among CC treatments (27.31 Mg ha −1 ). Stocks with standing and hayed CCs were greater than fallow (24.79 Mg ha −1 ) which was similar to grazed CCs. However, in 2020, stocks were less with hayed CCs (21.80 Mg ha −1 ) compared to grazed or standing CCs (24.27 Mg ha −1 ) and all were similar to fallow. Mean weight diameter of water stable aggregates increased with standing and grazed CCs (2.89 mm) compared to fallow (1.67 mm) in both years but hayed CCs were greater than fallow in 1 yr. Findings suggest CCs can replace fallow to produce high‐quality forage while improving soil health but residue management is critical when CC productivity is low. Core Ideas: Cover crop productivity and nutritive value varied across years. Grazing had no effect on soil bulk density compared to non‐grazed cover crops or fallow. Grazed and non‐grazed cover crops increased soil organic carbon and water stable aggregates compared to fallow. Hayed cover crops had greater water stable aggregates than fallow in 1 of 2 yr. Grazing removed 26% cover crop biomass compared with 73% when hayed.